The impact of simvastatin intervention on the healing of bone, soft tissue, and TMJ cartilage in dentistry: a systematic review and meta-analysis - Swati Gupta; Massimo Del Fabbro; Jia Chang (International Journal of Implant Dentistry, 2019)
Abstract The review aimed at assessing the osteopromotive potential as well as soft tissue and temporomandibular joint (TMJ) cartilage healing properties of simvastatin by summarizing its efficacy on the current dental treatment of periodontal bone and soft tissue defects, and temporomandibular joint (TMJ) arthritis from the available animals and human studies. An electronic search was performed on MEDLINE, Scopus, and Cochrane Central Register of Controlled Trials (CENTRAL) using a combination of keywords. A hand search was undertaken on seven oral surgery journals. No limitation of publication year in the English language was placed. Controlled randomized animal and human clinical trials, as well as prospective comparative studies, were included. Data on the comparison of topical/systemic simvastatin on bone healing in intrabony and furcation defects, extraction sockets, distraction osteogenesis, as well as soft tissue healing in mucogingival grafting procedures and cartilage protection in TMJ arthritis were extracted from all the eligible studies. Studies with a minimum of ten participants and follow up at least 6 months were included. Ten animal studies and six clinical studies were included in this study. All the animal studies included a minimum of eight sites per group assessed clinically, histologically, and radiographically. All human studies included clinical and radiological evaluation. The results of the review show that simvastatin administration displays positive treatment outcomes in the full range of therapies investigated in the oral regions such as periodontal infection control, periodontal and alveolar bone regeneration, soft tissue grafting, TMJ inflammation reduction, and cartilage repair. Its mechanism includes stimulating bone formation, promoting soft tissue healing, increasing articular and condylar cartilage thickness, as well as reducing inflammation at surgical sites in TMJ disorders. Simvastatin administration is beneficial to the healing of oral bone and cartilage. More studies are desired to determine its potential in soft tissue healing.